Pneumocephalus presenting as a complication of chronic otitis media — a case report - Mathai, John (Springer-Verlag, 2009)
Pneumocephalus secondary to chronic otitis media is an extremely rare phenomenon. Despite its rarity, the sequelae of intracranial air associated with otitis media may be grave if misdiagnosed. In this report a case of pneumocephalus following chronic mastoid infection is presented and the possible mechanism, diagnostic measures and the management is discussed.